The Whirl Cookstove: A Novel Development for Clean Biomass Burning. Issue 4 (3rd May 2016) - Carbone, Francesco; Carlson, Ethan L.; Baroni, Daniele; Gomez, Alessandro
ABSTRACT: An innovation in cookstove design was developed through a simple change in the natural-draft air entrainment pattern. The new concept is based on the establishment of a whirl in the combustion chamber, with air being introduced only tangentially through lateral slots in the cookstove walls. The whirl configuration creates better mixing between fuel and oxidizer, more uniform burning, and a reduction in pollutant emissions. Water boiling tests revealed significant improvements with respect to the ordinary natural draft mode of operation, the so-called rocket mode, including: a 13% average increase in the thermodynamic efficiency and a decrease in total particulate emissions by 53%. In water simmering tests, the gain in thermodynamic efficiency is estimated at 24% and the reduction in particulate mass and number are 70% and 44%, respectively. The particle abatement is more significant for sizes larger than 0.5 um. A whirl retrofit can be introduced in almost any existing cookstove design and is well suited to scalable manufacturing of inexpensive stoves by casting them from an inexpensive mold.